Association of cancer with overactive bladder and impact of overactive bladder on mortality among cancer survivors: NHANES 1999-2018 - Bin Zhi; Pin Zhao; Liyuan Duan; Yuan Liu; Zhaowei Zhu; Xuepei Zhang (PLoS ONE, 2025)
Background Cancer is one of the leading causes of death worldwide. There is little knowledge on the association between cancer and risk of overactive bladder (OAB). Additionally, the impact of OAB on mortality among cancer survivors remains unknown. We aimed to examine the association between cancer and risk of OAB and investigate OAB associations with mortality outcomes in cancer survivors. Methods We analyzed data of the National Health and Nutrition Examination Survey from 1999 to 2018. Cancer status was identified through the NHANES questionnaire. OAB was diagnosed with a cumulative OAB Symptom Score ≥  3. Multivariable logistic analysis was performed to examine the relationship between cancer and OAB. Cox regression analysis was carried out to investigate the relationship between OAB and mortality in subjects with cancer. Results In total, this study included a cohort of 32,166 participants. Within the study population, the occurrence of cancer was observed in 9.606%, and OAB was prevalent in 20.167%. The findings from the logistic regression analyses indicated a heightened risk of OAB among individuals with cancer in comparison to those devoid of cancer. Results from subgroup analyses also revealed affirmative correlations between cancer and OAB. Furthermore, the diagnosis of cancer, irrespective of whether it was genitourinary, non-genitourinary, pelvic, or non-pelvic in nature, was found to be correlated with an increased risk of OAB. Within the cohort comprising 3,090 participants diagnosed with cancer, a total of 850 all-cause deaths were recorded during a median follow-up duration of 76 months. After accounting for multiple covariates, OAB was linked to an elevated risk of all-cause and cancer-specific mortality. Moreover, the influence of OAB on mortality from all causes was observed across various cancer types, including both genitourinary and non-genitourinary, as well as pelvic and non-pelvic cancers. Conclusions The investigation identified a noteworthy positive correlation between cancer and the likelihood of OAB. Moreover, OAB was significantly correlated with an elevated risk of mortality among individuals who had received a cancer diagnosis.